Buprenorphine Waiver Attitudes Among Primary Care Providers. (July 2022) - Lai, Benjamin; Croghan, Ivana; Ebbert, Jon O.
Background: Despite efforts to improve access to Medications for Opioid Use Disorder (MOUD), such as buprenorphine, the number of opioid overdoses in the United States continues to rise. In April 2021, the Department of Health and Human Services removed the mandatory training requirement to obtain a buprenorphine waiver; the goal was to encourage more providers to prescribe buprenorphine, thus improving access. Little is known about the attitudes on buprenorphine prescribing after this policy change. Objective: The primary objective was to assess attitudes among primary care providers toward the removal of the buprenorphine waiver training requirement. A secondary objective was to identify other barriers to prescribing buprenorphine. Methods: We conducted a survey between September 15 and October 13, 2021 to assess the overall beliefs on the effectiveness of MOUD and attitudes toward the removal of the waiver training, current knowledge of buprenorphine, current practice styles related to screening for and treating OUD, and attitudes toward prescribing buprenorphine in the future. This survey was sent to 890 Mayo Clinic primary care providers in 5 US states. Results: One hundred twenty-three respondents (13.8%) completed the survey; 35.8% respondents agreed that the removal of the waiver training was a positive step. These respondents expressed a greater familiarity with the different formulations, pharmacology, and titration of buprenorphine. This group was also more likely to prescribe (or continue to prescribe) buprenorphine in the future. Approximately one-third (34.4%) of respondents reported perceived institutional support in prescribing buprenorphine. This group expressed greater confidence in diagnosing OUD, had greater familiarity with the different formulations, pharmacology, and titration of buprenorphine, and was more likely to prescribe (or continue to prescribe) buprenorphine in the future. Respondents who have been in practice for 11 to 20 years since completion of training were most likely to refer all OUD patients to specialists. Conclusions: Results of our survey suggests that simply removing the mandatory waiver training requirement is insufficient in positively changing attitudes toward buprenorphine prescribing. A key barrier is the perceived lack of institutional support. Future studies investigating effective ways to provide such support may help improve providers' willingness to prescribe buprenorphine.